Identifying the sources and timing of ancient and medieval atmospheric lead pollution in England using a peat profile from Lindow bog, Manchester - Le Roux, Gaël; Weiss, Dominik; Grattan, John; Givelet, Nicolas; Krachler, Michael; Cheburkin, Andriy K.; Rausch, Nicole; Kober, Bernd; Shotyk, William (Journal of environmental monitoring, 2004)
A peat core from Lindow bog near Manchester, England, was precisely cut into 2 cm slices to provide a high-resolution reconstruction of atmospheric Pb deposition. Radiocarbon and 210Pb age dates show that the peat core represents the period ca. 2000 BC to AD 1800. Eleven radiocarbon age dates of bulk peat samples reveal a linear age-depth relationship with an average temporal resolution of 18.5 years per cm, or 37 years per sample. Using the Pb/Ti ratio to calculate the rates of anthropogenic, atmospheric Pb deposition, the profile reveals Pb contamination first appearing in peat samples dating from ca. 900 BC which clearly pre-date Roman mining activities. Using TIMS, MC-ICP-MS, and SF-ICP-MS to measure the isotopic composition of Pb, the 208Pb/206Pb and 206Pb/207Pb data indicate that English ores were the predominant sources during the pre-Roman, Roman, and Medieval Periods. The study shows that detailed studies of peat profiles from ombrotrophic bogs, using appropriate preparatory and analytical methods, can provide new insight into the timing, intensity, and predominant sources of atmospheric Pb contamination, even in samples dating from ancient times.